KUALITAS AUDIT SEBAGAI PEMODERASI PENGARUH PERGANTIAN MANAJEMEN DAN AUDIT FEE PADA AUDITOR SWITCHING - Udayani, Ni Kadek Sri; Badera, I Dewa Nyoman (E-Jurnal Akuntansi, 2017)
This study has the objective of identifying and demonstrate empirically the effect of management changes and audit fees on auditor switching with audit quality as moderating variables. This research was conducted in the manufacturing sector companies listed on the Indonesian Stock Exchange (BEI) 2011-2015. The population in this study amounted to 147 companies, using purposive sampling techniques acquired sample number of 23 companies. Data analysis technique used is the logistic regression analysis and Moderating Regression Analysis (MRA). The results is managamenet changes in a positive effect on auditor switching. Variable audit fees, audit quality interactions with management changes, and the interaction with audit fee do not affect on auditor switching.
Keywords: Auditor Switching, Management Change, Audit Fee, Audit Quality.